2021
DOI: 10.21831/pri.v4i1.40381
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning: The Role Of Academic Self-Efficacy In Creating Academic Flow

Abstract: The spread of Covid-19 encourages educational institution to maximize online learning. Online learning can work well if students are able to focus on learning. The ability to focus on learning is known as academic flow. This study aims to explain effect of academic self-efficacy on flow academic in online learning. This research involve 296 participants who were selected by incidental sampling. The instruments used in this research are self-efficacy scale and flow short scale which were analyzed by using linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
(30 reference statements)
1
10
1
Order By: Relevance
“…They also mentioned some reasons such as background knowledge, the experience of vicarious, public encouragement, and affective factors which are significant in learners’ self-efficacy during online education. Pantu (2021) , in his study, revealed that learner self-efficacy influences academic flow in online learning situations. They argued that independent learning is the key point in online learning contexts and self-efficacious learners can control and manage their learning properly, and perform their online tasks smoothly.…”
Section: Review Of Literaturementioning
confidence: 98%
“…They also mentioned some reasons such as background knowledge, the experience of vicarious, public encouragement, and affective factors which are significant in learners’ self-efficacy during online education. Pantu (2021) , in his study, revealed that learner self-efficacy influences academic flow in online learning situations. They argued that independent learning is the key point in online learning contexts and self-efficacious learners can control and manage their learning properly, and perform their online tasks smoothly.…”
Section: Review Of Literaturementioning
confidence: 98%
“…with various variables in research, including motivation, academic success, procrastination, academic flow, academic resilience, and academic burnout (Erdianto & Dewi, 2020;Pantu, 2021b;Permatasari, Sutanto, et al, 2021;Svartdal et al, 2021). From these various studies, academic self-efficacy can be a robust predictor in influencing other variables.…”
Section: Pandemicmentioning
confidence: 99%
“…The impact of academic self-efficacy on academic performance is so high because students with high academic self-efficacy also tend not to experience academic procrastination (Khotimatussannah et al, 2021;Li et al, 2020;Malkoç & Mutlu, 2018;Rahmadina et al, 2020). In addition, students with high academic self-efficacy also have an academic flow to focus on completing the tasks given during online learning (Pantu, 2021b).…”
Section: Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy was found to be related to procrastination, academic flow, and academic performance (Khotimatussannah et al, 2021;Pantu, 2021;Rahmadina et al, 2020). Furthermore, self-efficacy is a variable that can predict an individual's mental health.…”
Section: Introductionmentioning
confidence: 99%